STRATEGI KEPALA SEKOLAH DALAM MENARIK MINAT CALON PESERTA DIDIK DI SD INPRES PALUPI KECAMATAN TATANGA KOTA PALU - Mubaraq A.Nongtji, Adry; Muhammad Ikhlasul Irsyad, Andi; Rafli, Moh; Jaya Lestari, Gita; M. Taul, Siskawati; Ilham, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the principal's strategy in attracting the interest of prospective new students at SD Inpres Palupi, Tatanga District, Palu City, and its supporting and inhibiting factors. This descriptive qualitative study collected data through triangulation of interviews, observations, and documentation. Data were analyzed using the Miles and Huberman interactive model. The results show that the principal's strategy is effective through POAC functions: SWOT-based planning, organizing an integrated admission team, actuating through a mix of print, social media (Instagram/TikTok), and word-of-mouth marketing, and controlling via class capacity monitoring. The main supporting factors are the strategic location in the BTN Palupi Permai residential center, teacher cohesiveness, and documented achievements. The inhibiting factors are infrastructure limitations (laboratories, libraries, prayer rooms) and zoning administrative barriers. This study implies the importance of accelerating teachers' digital literacy and the urgency of proposing facility expansion to the Department of Education.